(untitled) (ENTHYMEMA, 2020)
We propose an itinerary through the many readers characters in Italo Calvino narrative work, who eventually lead up to the Reader, the protagonist of If on a Winter’s Night a Traveler. From this comparison it is possible to deduce the re-emergence in the Traveler of the need of a correlation between the written world and the unwritten world. However, the terms of this relationship are now completely unbalanced in favor of the written world, the last bulwark against those «cose vaghe come i sentimenti, come il senso della vita» which invalidate the comprehension of the real world.